Anabolic steroids activate calcineurin–NFAT signaling and thereby increase myotube size and reduce denervation atrophy. (5th January 2015) - Qin, Weiping; Pan, Jiangping; Wu, Yong; Bauman, William A.; Cardozo, Christopher
Highlights: Calcineurin activity declined and NFATc4 was excluded from the nucleus in denervated muscle. Nandrolone increased calcineurin–NFAT signaling in myoblasts and denervated muscles. Nandrolone induced myoblast hypertrophy and protected against denervation atrophy. These data identify calcineurin–NFAT signaling as a novel target for androgen action. Abstract: Anabolic androgens have been shown to reduce muscle loss due to immobilization, paralysis and many other medical conditions, but the molecular basis for these actions is poorly understood. We have recently demonstrated that nandrolone, a synthetic androgen, slows muscle atrophy after nerve transection associated with down-regulation of regulator of calcineurin 2 (RCAN2), a calcineurin inhibitor, suggesting a possible role of calcineurin–NFAT signaling. To test this possibility, rat gastrocnemius muscle was analyzed at 56 days after denervation. In denervated muscle, calcineurin activity declined and NFATc4 was excluded from the nucleus and these effects were reversed by nandrolone. Similarly, nandrolone increased calcineurin activity and nuclear NFATc4 levels in cultured L6 myotubes. Nandrolone also induced cell hypertrophy that was blocked by cyclosporin A or overexpression of RCAN2. Finally protection against denervation atrophy by nandrolone in rats was blocked by cyclosporin A. These results demonstrate for the first time that nandrolone activates calcineurin–NFAT signaling, and that such signaling is important in nandrolone-induced cell hypertrophy and protection against paralysis-induced muscle atrophy.